Tradisi ruwatan jawa ditinjau dari urf dan pendekatan sosiologi hukum islam - Widodo, Joko; Yasir, Moh; Halim, Abdul (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The Javanese ruwatan tradition is a tradition that has been going on for a long time in Indonesia, especially on the island of Java, which has been carried out from generation to generation and has been preserved by the practitioners of this tradition. This tradition has the aim of ensuring that humans are given safety, sustenance and blessings because they have removed the sengkala from the human limbs or body. This article needs to be studied in depth, so this writing aims for the reader to increase knowledge about the views of the Javanese ruwatan tradition in terms of Urf and the Sociology of Islamic Law approach. This research uses a qualitative research approach with a description method, namely research that examines and describes the Javanese ruwatan tradition from a urf perspective and an Islamic legal sociological approach, as the main data is from the literature. The results of the research show that the Javanese ruwatan tradition which does not conflict with Islamic law, can be included as urf Sahih or a tradition that is in harmony with Islamic law, and ruwatan in the form of a celebration held by reading verses from the holy Qur'an, such as Surah Yasin and reading several Sholawat of the Prophet SAW, with the intention of asking Allah SWT for safety and good luck, this is permitted.